Critical Discourse Analysis of Additional Information in Skincare Products - Burhanudin Rais; Suhardi Suhardi; Rr.Putri Intan Permata Sari (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2020)
Research that analyses critically on claims and additional information on a skincare product is a research that bring the novelty in critical discourse analysis, because the previous study focused on the advertisement or the packaging. Although most skincare products apply this method (using claims and additional information), researchers focus on one of the branded skincare products; Pond’s. The main reason is; this product is already widely known and used by the people in Indonesia. Trough critical discourse analysis model from van Dijk, the researchers discuss three dimensions (text, social cognition and social context) in claims and additional information in some products from Pond’s. There are seven Pond’s products as the data in this study. Besides, researchers used additional data in the form of a survey to five skincare products users. The results of the analysis are; (1) on the text dimension, the general aim is to attract the consumers to choose Pond’s as their skincare products. (2) In social cognition, company show marketing techniques that try to obscure the facts in additional information by using small and separated text. (3) In the social context, the influence of consumers who are easily attracted to a product because of the interesting slogan text makes Pond’s use the hyperbole language